Demonstration of the asymmetric effect of CC-1065 on local DNA structure using a site-directed adduct in a 117-base-pair fragment from M13mp1. - Hurley, L H (1987)
Using DNase I and Alu I endonuclease analysis of a site-directed CC-1065-[N3-adenine]DNA adduct in a 117-base-pair fragment from M13mp1 DNA, we have demonstrated that CC-1065 produces an asymmetric effect on DNA conformation that extends more than one helix turn to the 5' side of the covalently modified adenine. CC-1065 is a potent antitumor antibiotic produced by Streptomyces zelensis, which is believed to mediate its cytotoxic effects through covalent binding to DNA. Previous studies have demonstrated that CC-1065 binds covalently to N3 of adenine and lies within the minor groove of DNA spanning a 4-base-pair sequence to the 5' side of the modified adenine. DNase I footprinting of this site-directed CC-1065-DNA adduct on the noncovalently modified strand shows that inhibition of cleavage occurs over a 12-base region, which is bordered on the 3' side by a site of 2-fold enhancement of cleavage. On the covalently modified strand a much less pronounced inhibition/enhancement pattern of cleavage occurs as far as 11 bases to the 5' side of the covalently modified adenine. While Hae III is able to cleave the DNA on both strands on the 3' side of the covalently modified adenine, Alu I is only able to cleave the covalently modified strand on the 5' side of the adduct. By taking into account the recently published structure of DNase I, we are able to interpret these results and develop a model for the effect of CC-1065 on local DNA structure. In this model, we propose selective drug-induced distortion of the covalently modified strand as a consequence of the alkylation of adenine by CC-1065.